Design, synthesis, and fungicidal activities of imino diacid analogs of valine amide fungicides. Issue 24 (15th December 2015) - Sun, Man; Yang, Hui-Hui; Tian, Lei; Li, Jian-Qiang; Zhao, Wei-Guang
Graphical abstract: Abstract: The novel imino diacid analogs of valine amides were synthesized via several steps, including the protection, amidation, deprotection, and amino alkylation of valine, with the resulting structures confirmed by 1 H and 13 C NMR and HRMS. Bioassays showed that some of these compounds exhibited good fungicidal activity. Notably, isopropyl 2-((1-((1-(3-fluorophenyl)ethyl)amino)-3-methyl-1-oxobutan-2-yl)amino)propanoate5i displayed significant levels of control, at 50%, against Erysiphe graminis at 3.9 μM as well as a level of potency very similar to the reference azoxystrobin, which gave 60% activity at this concentration. The present work demonstrates that imino diacid analogs of valine amides could be potentially useful key compounds for the development of novel fungicides against wheat powdery mildew.